PENERAPAN METODE PEMBELAJARAN EPA (EKSPLORASI, PENGENALAN DAN APLIKASI KONSEP) UNTUK MENINGKATKAN HASIL BELAJAR - Arnasari Merdekawati Hadi; Kafnun Fitriah (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2019)
The low learning outcomes of students in VII-A grade of SMP AlIkhwan Salama in Bima City is suspected that one of the causes is that there are still many students who experience difficulties in understanding the mathematical concepts being thought. As well as in delivering subject matter, more teachers apply teaching methods that are monotonous and less varied. As a result students become less active and only accept what is given by the teacher and do the assignment in accordance with what is asked by the teacher. Therefore, teachers need to find better learning methods so that the learning process that is endeavored can improve student learning outcomes, one of which is the EPA method. The purpose of this study is to improve student learning outcomes through the EPA method. This type of research is classroom action research (CAR) which takes place in three cycles. This study uses the EPA method (Exploration, Introduction and Application of concept). Data collection techniques used were tests and observation. Data analysis techniques using qualitative analysis. Based on the results of the study showed an increase in mastery learning from the average value of students in the first cycle of 70,51 with a percantage of 74,28% and the average value in the second cycle of 73,82 with a percentage of 80% and the average value in the third cycle of 80,05 with percentage of 88,57%. So it can be concluded that the application of the EPA (Exploration, Introduction, and Application of concepts)learning method on the subject matter of quadrilateral can improve mathematics learning outcomes of students.